2010
DOI: 10.1038/hr.2010.77
|View full text |Cite
|
Sign up to set email alerts
|

Effects of long-term treatment for obstructive sleep apnea on pulse wave velocity

Abstract: Continuous positive airway pressure (CPAP) treatment improves endothelial function and sympathetic activity in patients with obstructive sleep apnea (OSA). However, the long-term effects of CPAP on pulse wave velocity (PWV), which reflects arterial stiffness that is associated with cardiovascular events, have not been evaluated in OSA patients with or without hypertension (HT). In this study, 212 male OSA patients who had been receiving CPAP treatment for 2 years and were divided into two groups, those with HT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 29 publications
(45 reference statements)
1
32
0
Order By: Relevance
“…Similarly, Shiina et al 63 found 3 months of CPAP to lead to a significant decrease in baPWV but not peripheral blood pressure. Saito et al, 64 however, found 6 months of CPAP treatment to decrease both baPWV and peripheral blood pressure in both hypertensive and normotensive patients. Interestingly, following the significant decrease observed after the first 6 months of treatment, baPWV gradually increased in both groups over the following 18 months under study, whereas peripheral blood pressure did not.…”
Section: Resultsmentioning
confidence: 97%
“…Similarly, Shiina et al 63 found 3 months of CPAP to lead to a significant decrease in baPWV but not peripheral blood pressure. Saito et al, 64 however, found 6 months of CPAP treatment to decrease both baPWV and peripheral blood pressure in both hypertensive and normotensive patients. Interestingly, following the significant decrease observed after the first 6 months of treatment, baPWV gradually increased in both groups over the following 18 months under study, whereas peripheral blood pressure did not.…”
Section: Resultsmentioning
confidence: 97%
“…This observation remained significant even after adjustment for change of the blood pressure; therefore, metabolic syndrome may accelerate age-related increase of structural arterial stiffness. Sleep apnea is also a risk factor for accelerated increase of the brachial-ankle PWV 32,33) . Sympathetic nervous activation induced by hypoxia resulting from apnea may be one of the mechanisms underlying the accelerated increase of the arterial stiffness in subjects with sleep apnea 34) .…”
Section: Metabolic Syndrome Sleep Apnea and Obesitymentioning
confidence: 99%
“…Several studies have reported that continuous positive airway pressure therapy decreases blood pressure and PWV in SDB patients with hypertension in both the short‐term and long‐term 37, 38, 39. Additionally, meta‐analysis has demonstrated that continuous positive airway pressure improves aortic stiffness in patients with OSA 40.…”
Section: Discussionmentioning
confidence: 99%